High-Energy-Density Physics Fundamentals, Inertial Fusion, and Experimental Astrophysics - Drake, R. Paul.; Davison, Lee.; Horie, Yasuyuki; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2006)
The raw numbers of high-energy-density physics are amazing: shock waves at hundreds of km/s (approaching a million km per hour), temperatures of millions of degrees, and pressures that exceed 100 million atmospheres. This book introduces the reader to the fundamental tools and discoveries of high-energy-density physics. It surveys the production of high-energy-density conditions, the fundamental plasma and hydrodynamic models that can describe them and the problem of scaling from the laboratory to the cosmos. Connections to astrophysics are discussed throughout. The book is intended to support coursework in high-energy-density physics, to meet the needs of new researchers in this field, and also to serve as a useful reference on the fundamentals. Specifically the book has been designed to enable academics in physics, astrophysics, applied physics and engineering departments to provide in a single-course introduction to fluid mechanics and radiative transfer, with dramatic applications in the field of high-energy-density systems.
to High-Energy-Density Physics -- Descriptions of Fluids and Plasmas -- Properties of High-Energy-Density Plasmas -- Shocks and Rarefactions -- Hydrodynamic Instabilities -- Radiative Transfer -- Radiation Hydrodynamics -- Creating High-Energy-Density Conditions -- Inertial Confinement Fusion -- Experimental Astrophysics -- Relativistic High-Energy-Density Systems.
Keywords: Physics; Fluids; Astrophysics; Space sciences; Nuclear physics; Atoms; Matter; Plasma (Ionized gases).; Physics; Particle and Nuclear Physics; Atoms and Molecules in Strong Fields, Laser Matter Interaction; Plasma Physics; Astrophysics and Astroparticles; Fluid- and Aerodynamics; Extraterrestrial Physics, Space Sciences; Electronic books